Psychotic experiences and PTSD: exploring associations in a population survey. Issue 13 (20th May 2015) - Alsawy, S.; Wood, L.; Taylor, P. J.; Morrison, A. P.
Abstract : Background: Extensive evidence has shown that experiencing a traumatic event and post-traumatic stress disorder (PTSD) are associated with experiences of psychosis. However, less is known about specific PTSD symptoms and their relationship with psychotic experiences. This study aimed to examine the relationship between symptoms of PTSD with paranoia and auditory hallucinations in a large-scale sample. Method: The Adult Psychiatric Morbidity Survey (APMS) was utilized to examine the prevalence of lifetime trauma, symptoms of PTSD, and experiences of paranoia and auditory hallucinations ( n = 7403). Results: There were significant bivariate associations between symptoms of PTSD and psychotic experiences. Multiple logistic regression analyses indicated that reliving and arousal symptoms were significant predictors for paranoia while reliving, but not arousal symptoms, also significantly predicted auditory hallucinations. A dose-response relationship was found, the greater the number of PTSD symptoms, the greater the odds were of experiencing both paranoia and hallucinations. Conclusions: These findings illustrate that symptoms of PTSD are associated with increased odds of experiencing auditory hallucinations and paranoia. Overlaps appear to be present between the symptoms of PTSD and psychotic experiences. Increasing awareness of this association may advance work in clinical practice.